Pengaruh Pemberian Tepung Terigu dan Tepung Sagu Terhadap Kualitas Kimia Kamaboko Ikan Toman (Channa micropeltes) - Evnaweri Evnaweri; Natallo Bugar (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This reasearch aims to determine the formulation of flour and sago flour which is good and to know the effect of giving wheat flour and sago flour to the chemical quality of kamaboko Indonesian snakehead (Channa micropeltes). The benefits of the research as information about the right formulation and as information about the effect of giving wheat flour and sago flour to the chemical quality of Kamaboko Indonesian snakehead. This reasearch was conducted for 4 (four) months at Laboratory Processing of Fishery Product, Fisheries Department of Palangka Raya University. The data were collected based on the results of chemical testing, namely the test of moisture content, protein content, fat content, ash content and carbohydrate content. Based on the results of the chemical test, the best treatment determined by the effectiveness index method shows that treatment B (6% flour and 4% sago flour) is the best treatment because it has the highest value of 4.29. Keywords : Indonesian Snakehead (Channa micropeltes), kamaboko, wheat flour, sago flour, chemical quality.